Effects of Operating Room Noise on Patient Outcomes and Medical Staff: A Systematic Review - Xingsun Li; Jiang Li; Zhihui Xu; Yanfen Shang; Haidan Shi (Noise and Health)
Objective: High noise levels in operating rooms are a common problem in clinical practice. The aim of this study is to review the current study systematically to clarify the effects of operating room noise on medical staff and patients. Methods: We searched the studies on operating room noise published in PubMed, Web of Science, and Cochrane Library from 2014 to 2024. The study types included randomized controlled trials, case–control studies, and cohort studies. Study languages were not limited. Two researchers screened the study in accordance with inclusion and exclusion criteria and extracted relevant data for quality evaluation. Results: Ten studies were included in this systematic review. They involved 1485 subjects, comprising 888 patients and 597 healthcare workers. In the included studies, the operating room noise level generally exceeded 50 dB, and the recorded highest average noise level was 72.4 dB. Five studies investigated the effects of noise on the psychological state of operating room staff, involving 581 participants, and primarily reported that noise exposure led to adverse psychological effects, such as decreased attention and increased anxiety. Three studies, encompassing 114 participants, examined the physiological effects of noise on operating room staff and found that noise contributed to fatigue, headaches, and increased cortisol secretion. Additionally, five studies explored the influence of noise on surgical patients. Of these studies, four studies documented negative outcomes in patients, including postoperative infections and anxiety, whereas one demonstrated that low-level noise stimulation could beneficially improve postoperative delirium and pain in patients. Conclusion: Noise has a potential negative effect on staff and patients, underscoring the importance of implementing noise control measures in the operating room.